Common motifs, Characters, Metaphors and Plots between Dovlatov’s and Petrov’s Novels - Zaytseva, Svetlana Aleksandrovna (Opción, 2019)
The aim of the study is to investigate common motifs, characters, metaphors and plots between Dovlatov’s and Petrov’s novels via structural and comparative-historical methods. As a result, it is worth paying attention to the importance of the Russian intelligentsia metaphor. Refer to Dovlatov’s A Foreign Woman, where he, through the image of Maria Tatarovich, defines the significance of the Soviet intelligentsia: In the Soviet Union she was a multi-skilled intellectual. In conclusion, all of the novels have common motifs, metaphors, characters united with external similarity, actions, characteristics and plots